2014
DOI: 10.1152/ajprenal.00111.2014
|View full text |Cite
|
Sign up to set email alerts
|

First D1-like receptor PET imaging of the rat and primate kidney: implications for human disease monitoring

Abstract: Granda ML, Schroeder FA, Borra RH, Schauer N, Aisaborhale E, Guimaraes AR, Hooker JM. First D 1-like receptor PET imaging of the rat and primate kidney: implications for human disease monitoring. Am J Physiol Renal Physiol 307: F116 -F121, 2014. First published May 7, 2014 doi:10.1152/ajprenal.00111.2014.-The intrarenal dopamine system is important for signaling and natriuresis, and significant dysfunction is associated with hypertension and kidney disease in ex vivo studies. Dopamine receptors also modulate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…Dopamine released from dendritic cells has been shown to display a novel function in terms of inducing the differentiation of Th17 cells and causing experimental autoimmune encephalitis (Nakano et al, 2008) and antigen-induced neutrophilic airway inflammation (Nakagome et al, 2011). The drugs targeting dopamine D 1 receptors may be useful in the treatment of a wide range of disorders, including Parkinson's disease (Rascol et al, 2001), schizophrenia (Mu et al, 2007), hypertension (Granda et al, 2014), allergy and autoimmune diseases (Nakagome et al, 2011;Nakano et al, 2008 ).…”
Section: Discussionmentioning
confidence: 99%
“…Dopamine released from dendritic cells has been shown to display a novel function in terms of inducing the differentiation of Th17 cells and causing experimental autoimmune encephalitis (Nakano et al, 2008) and antigen-induced neutrophilic airway inflammation (Nakagome et al, 2011). The drugs targeting dopamine D 1 receptors may be useful in the treatment of a wide range of disorders, including Parkinson's disease (Rascol et al, 2001), schizophrenia (Mu et al, 2007), hypertension (Granda et al, 2014), allergy and autoimmune diseases (Nakagome et al, 2011;Nakano et al, 2008 ).…”
Section: Discussionmentioning
confidence: 99%
“…In 15 MS subjects (10 SPMS, 5 RRMS) and 11 controls, blood data were sampled from an arterial line during the 90-minutes PET acquisition (2 ml every 6 seconds during the first 3 minutes and at 5-, 10-, 20-, 30-, 60- and 90-minutes post-injection) to generate an arterial plasma input function. Plasma metabolite analysis was performed as previously outlined 28 . In the remaining subjects blood data were not collected either because they preferred not to undergo arterial line placement (N=13) or because an anesthesiologist was not available during PET (N=2).…”
Section: Methodsmentioning
confidence: 99%
“…Plasma metabolite analysis was performed as previously outlined. 28 In the remaining subjects, blood data were not collected either because subjects preferred not to undergo arterial line placement (n 5 13) or because an anesthesiologist was not available during PET (n 5 2).…”
Section: Imaging Data Acquisitionmentioning
confidence: 99%
“…[ 11 C]NNC 112, a PET radioligand for D1-like receptors, has previously been used to probe D1-like receptors in the human central nervous system. Granda et al [25] described in-vivo measurement of D1-like receptors in the renal cortex of Sprague-Dawley rat and the Papio anubis baboon by using [ 11 C]NNC 112. They demonstrated that the [ 11 C]NNC 112 binding in the kidney was self-saturable, specific and responsive to drug treatment.…”
Section: Localization and Regulation Of Renal Dopamine Receptorsmentioning
confidence: 99%
“…They demonstrated that the [ 11 C]NNC 112 binding in the kidney was self-saturable, specific and responsive to drug treatment. The use of PET imaging provides a new tool to investigate intrarenal dopamine function in animal models and in humans [25]. …”
Section: Localization and Regulation Of Renal Dopamine Receptorsmentioning
confidence: 99%